Comparison of toxicity following different conditioning regimens (busulfan/melphalan and carboplatin/etoposide/melphalan) for advanced stage neuroblastoma: Experience of two transplant centers. (28th November 2015) - Elborai, Yasser; Hafez, Hanafy; Moussa, Emad A.; Hammad, Mahmoud; Hussein, Hany; Lehmann, Leslie; Elhaddad, Alaa
Abstract: The outcome for advanced neuroblastoma has improved with combined modality therapy: induction chemotherapy, surgery, and consolidation with high‐dose chemotherapy/autologous HSCT, followed by local radiation, cisretinoic acid, and recently antibody therapy. In the United States, the most common conditioning regimen is CEM, while in Europe/Middle East, Bu/Mel has been widely used; it remains unclear which regimen has the best outcome. Assess renal, hepatic, and infectious toxicity through Day+100 in 2 different regimens. Retrospective comparison between CEM‐DFCHCC Boston and Bu/Mel‐ CCHE‐57357. Thirty‐five patients, median age 4, in Boston (2007–2011) and 38 patients, median age 3, in Cairo (2009–2011). Renal toxicity; creatinine was significantly higher in CEM than Bu/Mel: 57% (median day+90) vs. 29% (median>day+100), p = 0.004. One CEM patient died from renal dialysis at day+19. Hepatic toxicity was significantly higher in CEM than Bu/Mel: 80% (median day+26) vs. 58% (median day+60), p = 0.04. In infectious complications with CEM 14%, bacteremia (n = 4) and fungemia (n = 1), 3 had culture‐negative sepsis requiring vasopressors. With Bu/Mel 18%, bacteremia (n = 7), none required pressors, p = 0.4. Bu/Mel was associated with less acute hepatic and renal toxicity and thus may be preferable for preserving organ functions.